Clean And Healthy Lifestyle Behavior Education Program to Improve Personal Hygiene in Elementary School - Shalshabilla, Alysha Titania; Mukhtarudin, Kuntafie Al Haq; Pamudji, Raden; Ghiffari, Ahmad; Tusadiah, Halimah; Antoni, Antoni; Kurniatullah, Ridho; Prayoga, Randi; Muchsiri, Mukhtarudin (UKInstitute, 2023)
Clean and Healthy Living Behaviors (PHBS) are about all health practices used due to individual awareness for the family and its members to assist themselves in health and play a significant role in community activities. Such activity can protect against several illnesses, including infections. This activity aims to teach the students of SD Negeri 1 Karang Agung village about the meaning of PHBS and how it is applied. This exercise involves PHBS education, including using excellent and appropriate toothbrushes, the WHO six-step hand washing procedure, and disease information. The activities indicated that many SD Negeri 1 Karang Agung students still do not understand personal hygiene. Promoting the PBHS program at the school level and replicating similar activities in other villages or sub-district is recommended.